Development of a gelatin-based polyurethane vascular graft by spray, phase-inversion technology. (4th August 2015) - Losi, Paola; Mancuso, Luisa; Al Kayal, Tamer; Celi, Simona; Briganti, Enrica; Gualerzi, Alice; Volpi, Silvia; Cao, Giacomo; Soldani, Giorgio
Abstract: The capacity of a composite vascular graft constituting polyurethane (PU) and gelatin to support cell growth was investigated using human mesenchymal stem cells (hMSCs). Gelatin-based polyurethane grafts were fabricated by co-spraying polyurethane and gelatin using a spray, phase-inversion technique. Graft microstructure was investigated by light and scanning electron microscopy. Uniaxial tensile tests were performed to assess the grafts' mechanical properties in longitudinal and circumferential directions. hMSCs obtained from bone marrow aspirate were seeded onto flat graft samples. After 24, 48, and 72 h of incubation, cell morphology was evaluated by Giemsa staining and cell viability was calculated by XTT assay. SEM analysis evidenced that PU samples display a microporous structure, whereas the gelatin-based PU samples show a fibrillar appearance. The presence of cross-linked gelatin produced a significant increase of ultimate tensile strength and ultimate elongation in circumferential directions compared to PU material. Qualitative analysis of hMSC adhesion onto the grafts revealed remarkable differences between gelatin-based PU and control graft. hMSCs grown onto gelatin-based PU graft form a monolayer that reached confluence at 72 h, whereas cells seeded onto the control graft were not able to undergo appropriate spreading. hMSCs grown onto gelatin-based PU graft showed significantly higher viability than cells seeded onto bare PU at all time points. In conclusion, a composite vascular graft was successfully manufactured by simultaneous co-spraying of a synthetic polymer and a protein to obtain a scaffold that combines the mechanical characteristics of polyurethanes with the favorable cell interaction features of gelatin.